Diaphragm with gradient bulk density coating, preparation method of diaphragm, battery and electric equipment
By designing a gradient packing density coating in the diaphragm, the content of alumina and needle-shaped boehmite is adjusted layer by layer, the problem of poor dynamic performance of the diaphragm at high temperature is solved, and high heat resistance, high wetting and high liquid retention are achieved. diaphragm performance.
Patent Information
- Application Number
- CN202411664565.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-14
AI Technical Summary
In high temperature environments, existing ceramic diaphragms suffer from loss of electrolyte storage space and increased surface resistance due to the high bulk density of the coating, and their kinetic performance is sacrificed.
Using a coating with gradient bulk density, a multi-layer structure is formed by reducing the mass content of alumina layer by layer in the separator and increasing the mass content of acupuncture boehmite layer by layer to improve the high temperature resistance of the coating and electrolyte impregnation. performance.
The diaphragm size is basically unchanged under high temperature environments, the storage and diffusion ability of the electrolyte is improved, and the dynamic performance and heat resistance of the diaphragm are enhanced.
Smart Images

Figure CN119447689A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of diaphragm technology, and in particular to a diaphragm with a gradient stacking density coating, a preparation method thereof, a battery, and an electrical device. Background Art
[0002] In recent years, in order to further improve the high-temperature safety of battery cells and prevent the diaphragm from shrinking longitudinally or transversely in a high-temperature environment, resulting in direct contact between the positive and negative electrodes and a short circuit, more and more diaphragm manufacturers and scientific researchers are now focusing on smaller particle size powders and adhesives with better heat resistance, in order to obtain ceramic diaphragms with better heat resistance.
[0003] It is undeniable that the coating using small-particle powder and high-heat-resistant adhesive has good heat resistance, but because the small-particle powder in the high-heat-resistant coating is densely packed, the coating has a higher packing density, which determines that the coating has a certain loss of storage space for the electrolyte; on the other hand, due to the dense packing of small-particle powder, the surface resistance of the coating is higher than that of the powder coating with normal particle size, resulting in a certain sacrifice in the dynamics of the diaphragm.
[0004] Therefore, how to overcome the above problems is an issue that needs to be solved urgently. Summary of the invention
[0005] The purpose of the present application is to provide a diaphragm with a gradient stacking density coating and a preparation method thereof, a battery and an electrical device to solve the above-mentioned problems.
[0006] To achieve the above objectives, the present application provides, in a first aspect, a diaphragm having a gradient packing density coating, comprising a substrate and a coating, wherein at least one side of the substrate is provided with the coating;
[0007] The raw materials of the coating include aluminum oxide, needle-shaped boehmite, dispersant, adhesive, ether surfactant and water;
[0008] The coating layer includes multiple layers, the mass content of the aluminum oxide decreases layer by layer from the side adjacent to the substrate to the side away from the substrate, and the mass content of the needle-shaped boehmite increases layer by layer.
[0009] Optionally, the diaphragm having a gradient packing density coating satisfies at least one of the following conditions:
[0010] A. The D50 of the aluminum oxide is 100nm-500nm;
[0011] B. The length of the needle-shaped boehmite is 3 μm-15 μm;
[0012] C. The aspect ratio of the needle-shaped boehmite is 3-30:1;
[0013] D. The specific surface area of the needle-shaped boehmite is 6 g / m 2 -12g / m 2 ;
[0014] E. The thickness ratio of the coating to the substrate is 0.1-1:1;
[0015] H. The dispersant includes one or more of carboxylate fluorine dispersants, triethyl phosphate, sulfonate fluorine dispersants, sodium polyacrylate, potassium polyacrylate, and polyethylene glycol;
[0016] I. The adhesive includes one or more of polyacrylic acid, polyacrylonitrile and polyacrylamide;
[0017] J. The glass transition temperature of the adhesive is ≥150°C;
[0018] K. The ether surfactant includes one or more of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ether, and polyether-modified polysiloxane.
[0019] Optionally, the diaphragm having a gradient packing density coating satisfies at least one of the following conditions:
[0020] A. The D50 of the aluminum oxide is 200nm-400nm;
[0021] B. The length of the needle-shaped boehmite is 6 μm-12 μm;
[0022] C. The aspect ratio of the needle-shaped boehmite is 10-20:1;
[0023] D. The specific surface area of the needle-shaped boehmite is 7 g / m 2 -10g / m 2 ;
[0024] E. The glass transition temperature of the adhesive is ≥180°C.
[0025] Optionally, the coating includes a first coating, a second coating, and a third coating arranged in sequence, the first coating is adjacent to the substrate, and the coating satisfies at least one of the following conditions:
[0026] A. The thickness of the first coating is 0.5 μm-2 μm;
[0027] B. The thickness of the second coating is 1 μm-5 μm;
[0028] C. The thickness of the third coating is 1 μm-5 μm;
[0029] D. The mass fraction of aluminum oxide in the first coating is 89.3%-97.1%, and the mass fraction of the needle-shaped boehmite is 0%;
[0030] E. The mass fraction of aluminum oxide in the second coating is 30%-60%, and the mass fraction of the needle-shaped boehmite is 29.3%-67.1%;
[0031] G. The mass fraction of aluminum oxide in the third coating is 5%-40%, and the mass fraction of needle-shaped boehmite is 49.3%-92.1%;
[0032] H. The mass fraction of aluminum oxide in the second coating layer is 10%-40% higher than the mass fraction of aluminum oxide in the third coating layer.
[0033] Optionally, the diaphragm having a gradient packing density coating satisfies at least one of the following conditions:
[0034] A. The thickness of the first coating is 0.8 μm-1.5 μm;
[0035] B. The thickness of the second coating is 2 μm-4 μm;
[0036] C. The thickness of the third coating is 2 μm-4 μm;
[0037] D. the mass fraction of aluminum oxide in the second coating is 40%-55%;
[0038] E. The mass fraction of aluminum oxide in the third coating is 10%-30%;
[0039] F. The mass fraction of aluminum oxide in the second coating layer is 15%-30% higher than the mass fraction of aluminum oxide in the third coating layer.
[0040] The second aspect of the present application provides a method for preparing a diaphragm having a gradient stacking density coating, comprising:
[0041] Mixing the raw materials according to different mass contents to obtain a plurality of coating slurries;
[0042] The plurality of coating slurries are disposed on the surface of the substrate according to the mass content of aluminum oxide from high to low and the mass content of needle-shaped boehmite from low to high, so as to obtain a diaphragm having a gradient packing density coating.
[0043] Optionally, the mixing includes: first mixing necessary alumina, dispersant, water and non-essential needle-shaped boehmite to obtain a first mixture; second mixing the first mixture and an adhesive to obtain a second mixture; third mixing the second mixture and an ether surfactant; at least one of the following conditions is met:
[0044] A. The stirring speed of the first mixing is 10rpm-40rpm, the dispersion speed is 1000rpm-3000rpm, and the time of the first mixing is 30min-120min;
[0045] B. The stirring speed of the second mixing is 10rpm-40rpm, the dispersion speed is 1800rpm-4000rpm, and the time of the second mixing is 60min-180min;
[0046] C. The stirring speed of the third mixing is 10rpm-40rpm, the dispersion speed is 300rpm-1000rpm, and the time of the third mixing is 20min-60min;
[0047] D. The setting includes coating and drying.
[0048] Optionally, the plurality of coating slurries include a first coating slurry, a second coating slurry, and a third coating slurry.
[0049] The third aspect of the present application provides a battery, comprising the diaphragm with a gradient stacking density coating or the diaphragm with a gradient stacking density coating prepared by the preparation method of the diaphragm with a gradient stacking density coating.
[0050] A fourth aspect of the present application provides an electrical device, comprising the battery.
[0051] Compared with the prior art, the beneficial effects of this application include:
[0052] The present application provides a diaphragm with a gradient stacking density coating, in which alumina particles are densely stacked and the particles are tightly fixed by a high-temperature adhesive. Under high-temperature conditions, the lateral and longitudinal dimensions of the coating are substantially unchanged, so the coating has high-temperature resistance. The needle-shaped boehmite in the coating has a needle-shaped morphology, so the coating is relatively loosely stacked, and its weight per unit volume is lower than that of small-particle alumina. On the other hand, since the needle-shaped boehmite has an ultra-high specific surface area, the electrolyte can quickly infiltrate and diffuse in the coating, thereby improving the dynamic performance of the diaphragm. Alumina is embedded in the needle-shaped boehmite powder, which, on the one hand, increases the contact points of the needle-shaped boehmite, further increases and shortens the path for the diffusion and infiltration of the electrolyte, and further improves the diaphragm dynamics. On the other hand, Alumina is embedded in the loose needle-shaped boehmite coating, which can prevent the size of the needle-shaped boehmite from changing too much in a high-temperature environment and improve the heat resistance of the coating; the mass content of alumina decreases layer by layer from the side adjacent to the substrate to the side away from the substrate, and the alumina close to the substrate surface is more densely stacked, providing a support structure for the high-temperature environment and preventing the membrane size from changing significantly; the mass content of the needle-shaped boehmite increases layer by layer, so that the stacking density of the coating from the direction close to the substrate to the direction away from the substrate gradually decreases, the specific surface area increases, and it has excellent electrolyte wettability, so that the coating has higher porosity, giving the membrane ultra-high electrolyte storage capacity and electrolyte rapid infiltration ability, so that the obtained membrane with a gradient stacking density coating has high heat resistance, high wettability and high liquid retention rate.
[0053] The method for preparing a diaphragm with a gradient stacking density coating provided in the present application is simple to operate.
[0054] The battery provided in the present application has a small shrinkage of the diaphragm size under high temperature environment, which can effectively prevent the positive and negative electrodes from being short-circuited due to overhang anomalies, and the battery has high safety; the diaphragm has excellent electrolyte retention and diffusion properties, and the battery cell rate performance is good.
[0055] The electrical equipment provided in this application is not only suitable for conventional application scenarios, but also can be used in high-temperature and harsh application scenarios, and has the advantage of instantly releasing large amounts of electricity. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0057] Figure 1 This is a schematic diagram of the structure of the diaphragm with gradient stacking density coating prepared in Example 1;
[0058] Figure 2This is a physical picture of the diaphragm with gradient stacking density coating prepared in Example 1.
[0059] Description of main component symbols:
[0060] 100 - substrate; 200 - first coating; 300 - second coating; 400 - third coating. DETAILED DESCRIPTION
[0061] As used herein:
[0062] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0063] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0064] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0065] In these examples, parts and percentages are by mass unless otherwise indicated.
[0066] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.
[0067] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).
[0068] In a first aspect, the present application provides a diaphragm having a gradient packing density coating, comprising a substrate and a coating, wherein at least one side of the substrate is provided with the coating;
[0069] The raw materials of the coating include aluminum oxide, needle-shaped boehmite, dispersant, adhesive, ether surfactant and water;
[0070] The coating layer includes multiple layers, the mass content of the aluminum oxide decreases layer by layer from the side adjacent to the substrate to the side away from the substrate, and the mass content of the needle-shaped boehmite increases layer by layer.
[0071] In some embodiments, the diaphragm having a gradient packing density coating satisfies at least one of the following conditions:
[0072] A. The D50 of the aluminum oxide is 100nm-500nm;
[0073] Optionally, the D50 of aluminum oxide may be 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, or any value between 100 nm and 500 nm;
[0074] It should be noted that when the D50 of alumina is 100nm-500nm, alumina with a small particle size has a higher packing density and a high specific surface area, which can further improve the heat resistance of the coating and prevent the coating from having too many gaps in the middle, resulting in insufficient heat resistance.
[0075] B. The length of the needle-shaped boehmite is 3 μm-15 μm;
[0076] Optionally, the length of the needle-shaped boehmite may be 3 μm, 6 μm, 9 μm, 12 μm, 15 μm, or any value between 3 μm and 15 μm;
[0077] C. The aspect ratio of the needle-shaped boehmite is 3-30:1;
[0078] Optionally, the aspect ratio of the needle-shaped boehmite may be 3:1, 10:1, 20:1, 30:1 or any value between 3 and 30:1;
[0079] It should be noted that the aspect ratio is also the length-to-width ratio, that is, the ratio of the longest diameter through the interior of the particle to the longest diameter perpendicular to it;
[0080] It should be noted that when the aspect ratio of the needle-shaped boehmite is 3-30:1, the needle-shaped boehmite has a higher specific surface area, which is conducive to the rapid infiltration and diffusion of the electrolyte. At the same time, the aspect ratio gives the coating a knitted criss-cross morphology, which can reserve sufficient electrolyte storage space and improve the dynamic performance of the separator.
[0081] D. The specific surface area of the needle-shaped boehmite is 6 g / m 2 -12g / m 2 ;
[0082] Optionally, the specific surface area of the needle-shaped boehmite can be 6 g / m 2 , 9g / m 2 , 12g / m 2 Or 6g / m 2 -12g / m 2 Any value between
[0083] E. The thickness ratio of the coating to the substrate is 0.1-1:1;
[0084] Optionally, the thickness ratio of the coating layer to the substrate may be 0.1:1, 0.2:1, 0.4:1, 0.6:1, 0.8:1, 1:1 or any value between 0.1 and 1:1;
[0085] H. The dispersant includes one or more of carboxylate fluorine dispersants, triethyl phosphate, sulfonate fluorine dispersants, sodium polyacrylate, potassium polyacrylate, and polyethylene glycol;
[0086] I. The adhesive includes one or more of polyacrylic acid, polyacrylonitrile and polyacrylamide;
[0087] J. The glass transition temperature of the adhesive is ≥150°C;
[0088] Optionally, the glass transition temperature of the adhesive may be 150° C., 200° C., 300° C., 500° C., or any value greater than or equal to 150° C.;
[0089] K. The ether surfactant includes one or more of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ether, and polyether-modified polysiloxane.
[0090] In some embodiments, the diaphragm having a gradient packing density coating satisfies at least one of the following conditions:
[0091] A. The D50 of the aluminum oxide is 200nm-400nm;
[0092] Optionally, the D50 of aluminum oxide may be 200 nm, 250 nm, 280 nm, 320 nm, 350 nm, 400 nm, or any value between 200 nm and 400 nm;
[0093] B. The length of the needle-shaped boehmite is 6 μm-12 μm;
[0094] Optionally, the length of the needle-shaped boehmite may be 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm or any value between 6 μm and 12 μm;
[0095] C. The aspect ratio of the needle-shaped boehmite is 10-20:1;
[0096] Optionally, the aspect ratio of the needle-shaped boehmite may be 10:1, 12:1, 14:1, 16:1, 18:1, 20:1 or any value between 10 and 20:1;
[0097] D. The specific surface area of the needle-shaped boehmite is 7 g / m 2 -10g / m 2 ;
[0098] Optionally, the specific surface area of the needle-shaped boehmite can be 7 g / m 2 , 8g / m 2 , 9g / m 2 , 10g / m 2 or 7g / m 2 -10g / m 2 Any value between
[0099] E. The glass transition temperature of the adhesive is ≥180°C.
[0100] Optionally, the glass transition temperature of the adhesive may be 180°C, 200°C, 280°C, 380°C, 480°C, 580°C, or any value greater than or equal to 180°C.
[0101] In some embodiments, the coating comprises a first coating, a second coating, and a third coating arranged in sequence, the first coating is adjacent to the substrate, and the coating satisfies at least one of the following conditions:
[0102] It should be noted that the first coating is a high-stack density, high-temperature resistant small-particle alumina coating, which provides a high-temperature resistant bottom framework for the entire gradient stacking density coating; the second coating is a low-stack density, small-particle alumina and needle-shaped boehmite mixed coating, which has both certain heat resistance and excellent electrolyte absorption and retention properties. A suitable proportion of small-particle alumina fills part of the gaps, which improves the dimensional stability of the coating under high temperature conditions, while retaining a suitable electrolyte storage space, improving the coating's ability to retain liquid, and is beneficial to reducing the impedance of the battery cell; the third coating is an ultra-low stacking density, small-particle alumina and needle-shaped boehmite mixed coating, which has the lowest stacking density, abundant interlayer gaps, and ultra-high electrolyte wettability, which can achieve rapid diffusion and infiltration of the electrolyte;
[0103] It can be understood that the first coating is a small-particle alumina coating with a high stacking density and a thinner thickness, which can provide a high heat-resistant support structure, and the thinner thickness will not cause too much dynamic sacrifice; the small-particle alumina in the second coating can fill the gaps after the needle-shaped boehmite is stacked, thereby increasing the stacking density of the layer; the amount fraction of small-particle alumina in the third coating is lower than that of the second coating, so the third coating has the lowest stacking density and is more suitable for rapid infiltration and storage of electrolyte.
[0104] A. The thickness of the first coating is 0.5 μm-2 μm;
[0105] Optionally, the thickness of the first coating layer may be 0.5 μm, 1 μm, 1.5 μm, 2 μm, or any value between 0.5 μm and 2 μm;
[0106] B. The thickness of the second coating is 1 μm-5 μm;
[0107] Optionally, the thickness of the second coating layer may be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, or any value between 1 μm and 5 μm;
[0108] C. The thickness of the third coating is 1 μm-5 μm;
[0109] Optionally, the thickness of the third coating layer may be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm or any value between 1 μm and 5 μm;
[0110] D. The mass fraction of aluminum oxide in the first coating is 89.3%-97.1%, and the mass fraction of the needle-shaped boehmite is 0%;
[0111] Optionally, the mass fraction of aluminum oxide in the first coating layer may be 89.3%, 90%, 92%, 94%, 96%, 97.1%, or any value between 89.3% and 97.1%;
[0112] E. The mass fraction of aluminum oxide in the second coating is 30%-60%, and the mass fraction of the needle-shaped boehmite is 29.3%-67.1%;
[0113] Optionally, the mass fraction of aluminum oxide in the second coating layer may be 30%, 40%, 50%, 60% or any value between 30% and 60%, and the mass fraction of needle-shaped boehmite may be 29.3%, 40%, 50%, 60%, 67.1% or any value between 29.3% and 67.1%;
[0114] G. The mass fraction of aluminum oxide in the third coating is 5%-40%, and the mass fraction of needle-shaped boehmite is 49.3%-92.1%;
[0115] Optionally, the mass fraction of aluminum oxide in the third coating layer may be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or any value between 5% and 40%, and the mass fraction of needle-shaped boehmite may be 49.3%, 60%, 70%, 80%, 90%, 92.1% or any value between 49.3% and 92.1%;
[0116] H. The mass fraction of aluminum oxide in the second coating layer is 10%-40% higher than the mass fraction of aluminum oxide in the third coating layer.
[0117] Optionally, the mass fraction of aluminum oxide in the second coating layer may be 10%, 15%, 20%, 25%, 30%, 35%, 40% or any value between 10% and 40% higher than the mass fraction of aluminum oxide in the third coating layer.
[0118] In some embodiments, the diaphragm having a gradient packing density coating satisfies at least one of the following conditions:
[0119] A. The thickness of the first coating is 0.8 μm-1.5 μm;
[0120] Optionally, the thickness of the first coating layer may be 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm or any value between 0.8 μm and 1.5 μm;
[0121] B. The thickness of the second coating is 2 μm-4 μm;
[0122] Optionally, the thickness of the second coating layer may be 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, or any value between 2 μm and 4 μm;
[0123] C. The thickness of the third coating is 2 μm-4 μm;
[0124] Optionally, the thickness of the third coating layer may be 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, or any value between 2 μm and 4 μm;
[0125] D. the mass fraction of aluminum oxide in the second coating is 40%-55%;
[0126] Optionally, the mass fraction of aluminum oxide in the second coating layer may be 40%, 45%, 50%, 55% or any value between 40% and 55%;
[0127] E. The mass fraction of aluminum oxide in the third coating is 10%-30%;
[0128] Optionally, the mass fraction of aluminum oxide in the third coating layer may be 10%, 15%, 20%, 25%, 30% or any value between 10% and 30%;
[0129] F. The mass fraction of aluminum oxide in the second coating layer is 15%-30% higher than the mass fraction of aluminum oxide in the third coating layer.
[0130] Optionally, the mass fraction of aluminum oxide in the second coating layer may be 15%, 20%, 25%, 30% higher than the mass fraction of aluminum oxide in the third coating layer, or any value between 15% and 30%.
[0131] The second aspect of the present application provides a method for preparing a diaphragm having a gradient stacking density coating, comprising:
[0132] Mixing the raw materials according to different mass contents to obtain a plurality of coating slurries;
[0133] The plurality of coating slurries are disposed on the surface of the substrate according to the mass content of aluminum oxide from high to low and the mass content of needle-shaped boehmite from low to high, so as to obtain a diaphragm having a gradient packing density coating.
[0134] In some embodiments, the mixing includes: first mixing necessary alumina, dispersant, water and non-essential needle-shaped boehmite to obtain a first mixture; second mixing the first mixture and an adhesive to obtain a second mixture; third mixing the second mixture and an ether surfactant; and satisfying at least one of the following conditions:
[0135] It should be noted that the step-by-step mixing and the preparation of the first mixture require high-speed dispersion to mechanically shear and disperse the alumina and needle-shaped boehmite into single powder particles to form a uniform dispersion; the adhesive is easily demulsified under high-speed dispersion, so it must be mixed in steps;
[0136] A. The stirring speed of the first mixing is 10rpm-40rpm, the dispersion speed is 1000rpm-3000rpm, and the time of the first mixing is 30min-120min;
[0137] Optionally, the stirring speed of the first mixing can be 10rpm, 20rpm, 30rpm, 40rpm or any value between 10rpm-40rpm, the dispersion speed can be 1000rpm, 2000rpm, 3000rpm or any value between 1000rpm-3000rpm, and the first mixing time can be 30min, 60min, 90min, 120min or any value between 30min-120min;
[0138] In some optional embodiments, the stirring speed of the first mixing is 15 rpm-30 rpm, the dispersion speed is 1500 rpm-2500 rpm, and the time of the first mixing is 40 min-90 min;
[0139] In some embodiments, the first mixing, the second mixing, and the third mixing are performed in a stirring disperser with a double planetary stirring and a high-speed dispersing disk;
[0140] B. The stirring speed of the second mixing is 10rpm-40rpm, the dispersion speed is 1800rpm-4000rpm, and the time of the second mixing is 60min-180min;
[0141] Optionally, the stirring speed of the second mixing can be 10rpm, 20rpm, 30rpm, 40rpm or any value between 10rpm-40rpm, the dispersion speed can be 1800rpm, 3000rpm, 4000rpm or any value between 1800rpm-4000rpm, and the second mixing time can be 60min, 120min, 180min or any value between 60min-180min;
[0142] In some optional embodiments, the stirring speed of the second mixing is 15 rpm-30 rpm, the dispersion speed is 2000 rpm-3000 rpm, and the time of the second mixing is 80 min-150 min;
[0143] C. The stirring speed of the third mixing is 10rpm-40rpm, the dispersion speed is 300rpm-1000rpm, and the time of the third mixing is 20min-60min;
[0144] Optionally, the stirring speed of the third mixing can be 10rpm, 20rpm, 30rpm, 40rpm or any value between 10rpm-40rpm, the dispersion speed can be 300rpm, 600rpm, 1000rpm or any value between 300rpm-1000rpm, and the time of the third mixing can be 20min, 40min, 60min or any value between 20min-60min;
[0145] In some optional embodiments, the stirring speed of the third mixing is 15 rpm-30 rpm, the dispersion speed is 500 rpm-800 rpm, and the time of the third mixing is 30 min-50 min;
[0146] D. The setting includes coating and drying.
[0147] In some embodiments, the plurality of coating slurries include a first coating slurry, a second coating slurry, and a third coating slurry.
[0148] In some specific embodiments, the raw materials of the first coating slurry, calculated based on the total mass of 100%, include: 2%-20% of the aluminum oxide, 1%-6% of the mass of the dispersant, 2%-6% of the mass of the adhesive, 0.1%-1% of the ether surfactant, and the rest is water;
[0149] The raw materials of the second coating slurry, calculated based on the total mass of 100%, include: the total mass of the alumina and the needle-shaped boehmite is 2%-20%, wherein the alumina accounts for 30.9%-67.2% of the total mass of the alumina and the needle-shaped boehmite, the needle-shaped boehmite accounts for 32.8%-69.1% of the total mass of the alumina and the needle-shaped boehmite, the mass of the dispersant and the adhesive are 1%-6% and 2%-6% of the total mass of the alumina and the needle-shaped boehmite, respectively, the ether surfactant is 0.1%-1%, and the rest is water;
[0150] The raw materials of the third coating slurry, calculated based on the total mass being 100%, include: the total mass of the alumina and the needle-shaped boehmite is 2%-20%, wherein the alumina accounts for 5.1%-44.8% of the total mass of the alumina and the needle-shaped boehmite, the needle-shaped boehmite accounts for 55.2%-94.9% of the total mass of the alumina and the needle-shaped boehmite, the masses of the dispersant and the adhesive are 1%-6% and 2%-6% of the total mass of the alumina and the needle-shaped boehmite respectively, the ether surfactant is 0.1%-1%, and the rest is water.
[0151] The third aspect of the present application provides a battery, comprising the diaphragm with a gradient stacking density coating or the diaphragm with a gradient stacking density coating prepared by the preparation method of the diaphragm with a gradient stacking density coating.
[0152] It should be noted that the battery includes but is not limited to one or more of lithium-ion batteries and sodium-ion batteries, and is essentially applicable to any battery that requires a diaphragm.
[0153] A fourth aspect of the present application provides an electrical device, comprising the battery.
[0154] It should be noted that electrical equipment may be but is not limited to mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc.; among them, mobile devices may include but are not limited to at least one of mobile phones, laptop computers, etc.; electric vehicles may include but are not limited to at least one of pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.
[0155] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0156] Example 1
[0157] A first aspect of the present embodiment provides a diaphragm having a gradient stacking density coating, comprising a substrate and a coating, wherein the coating is disposed on one side of the substrate.
[0158] The structure of the diaphragm with gradient packing density coating is shown in FIG. Figure 1 As shown, the total thickness of the diaphragm is 14μm, the thickness of the substrate 100 is 9μm, the total thickness of the coating is 5μm, the thickness of the first coating 200 is 1μm, the mass fraction of small-particle alumina is 92.6wt% of the first coating, and the mass fraction of needle-shaped boehmite is 0; the thickness of the second coating 300 is 2μm, the mass fraction of small-particle alumina is 40wt% of the second coating 300, and the mass fraction of needle-shaped boehmite is 52.6wt%; the thickness of the third coating 400 is 2μm, the mass fraction of small-particle alumina is 15wt% of the third coating 400, and the mass fraction of needle-shaped boehmite is 77.6wt%.
[0159] The D50 of alumina is 200nm, the length of the needle-shaped boehmite is 9μm, the aspect ratio is 15:1, and the specific surface area is 6g / m 2 -12g / m2 The glass transition temperature of the adhesive polyacrylic acid is 200℃.
[0160] The second aspect of this embodiment provides a method for preparing a diaphragm having a gradient stacking density coating, and the specific steps are as follows:
[0161] S1: Preparation of the first coating slurry: Based on the total mass of the slurry being 100%, weigh the corresponding mass of materials according to which alumina accounts for 8% of the slurry mass fraction, dispersant sodium polyacrylate and adhesive polyacrylic acid respectively account for 4% of the mass fraction of small-particle alumina, ether surfactant polyether-modified siloxane is 0.5%, and the rest is water;
[0162] Alumina, sodium polyacrylate and water are added to a dispersion tank, and a stirring and dispersing machine with a double planetary stirring and a high-speed dispersing disk is used for stirring and dispersing, the stirring speed is 20 rpm, the dispersing speed is 2000 rpm, and the stirring and dispersing time is 60 minutes; then the adhesive polyacrylic acid is added, and the stirring is continued to be uniform, the stirring speed is 20 rpm, the dispersing speed is 2800 rpm, and the stirring and dispersing time is 120 minutes; finally, the surfactant polyether-modified siloxane is added, and the stirring and dispersing is carried out at a low speed, the stirring speed is 20 rpm, the dispersing speed is 600 rpm, and the stirring and dispersing time is 40 minutes, to obtain a first coating slurry;
[0163] S2: Preparation of the second coating slurry: Based on the total mass of the slurry being 100%, the mass fraction of alumina and needle-shaped boehmite being 10%, wherein alumina being 43.2% of the total mass of alumina and needle-shaped boehmite, needle-shaped boehmite being 56.8% of the total mass of alumina and needle-shaped boehmite, dispersant sodium polyacrylate and adhesive polyacrylic acid being 4% of the mass fraction of small-particle alumina, ether surfactant polyether-modified siloxane being 0.5%, and the rest being water, weigh the corresponding mass of the materials;
[0164] Alumina, sodium polyacrylate, sodium polyacrylate and water are added to a dispersion tank, and a stirring and dispersing machine with a double planetary stirring and a high-speed dispersing disk is used for stirring and dispersing, the stirring speed is 20rpm, the dispersing speed is 2000rpm, and the stirring and dispersing time is 60min; then the adhesive is added, and the stirring is continued to be uniform, the stirring speed is 20rpm, the dispersing speed is 2800rpm, and the stirring and dispersing time is 120min; finally, the surfactant polyether-modified siloxane is added, and the stirring and dispersing is carried out at a low speed, the stirring speed is 20rpm, the dispersing speed is 600rpm, and the stirring and dispersing time is 40min, to obtain a second coating slurry;
[0165] S3: Preparation of the third coating slurry: Based on the total mass of the slurry being 100%, the mass fraction of alumina and needle-shaped boehmite being 10%, wherein alumina is 16.2% of the total mass fraction of alumina and needle-shaped boehmite, needle-shaped boehmite is 83.8% of the total mass fraction of alumina and needle-shaped boehmite, dispersant sodium polyacrylate and adhesive polyacrylic acid are respectively 4% of the mass fraction of small-particle alumina, ether surfactant polyether-modified siloxane is 0.5%, and the rest is water. Weigh the corresponding mass of the materials;
[0166] Alumina, sodium polyacrylate, sodium polyacrylate and water are added to a dispersion tank, and a stirring and dispersing machine with a double planetary stirring and a high-speed dispersing disk is used for stirring and dispersing, the stirring speed is 20rpm, the dispersing speed is 2000rpm, and the stirring and dispersing time is 60min; then the adhesive is added, and the stirring is continued to be uniform, the stirring speed is 20rpm, the dispersing speed is 2800rpm, and the stirring and dispersing time is 120min; finally, the surfactant polyether-modified siloxane is added, and the stirring and dispersing is carried out at a low speed, the stirring speed is 20rpm, the dispersing speed is 600rpm, and the stirring and dispersing time is 40min, to obtain a third coating slurry;
[0167] S4: A PE diaphragm with a thickness of 9 μm and a porosity of 42% was selected, and a first coating slurry, a second coating slurry and a third coating slurry were sequentially coated and dried using a micro-concave roller coater.
[0168] The physical object of the diaphragm with gradient packing density coating is as follows Figure 2 shown.
[0169] A third aspect of the present application provides a lithium-ion battery, comprising the above-mentioned separator with a gradient stacking density coating.
[0170] Example 2
[0171] Difference from Example 1: The mass fraction of aluminum oxide in the second coating is 30%.
[0172] Example 3
[0173] Difference from Example 1: The mass fraction of aluminum oxide in the second coating layer is 60%.
[0174] Example 4
[0175] Difference from Example 1: The mass fraction of aluminum oxide in the third coating is 5%.
[0176] Example 5
[0177] The difference from Example 1 is that the mass fraction of aluminum oxide in the second coating layer is 60%, and the mass fraction of aluminum oxide in the third coating layer is 40%.
[0178] Example 6
[0179] Difference from Example 1: The aspect ratio of the needle-shaped boehmite is 3:1.
[0180] Example 7
[0181] Difference from Example 1: The aspect ratio of the needle-shaped boehmite is 30:1.
[0182] Comparative Example 1
[0183] The difference from Example 1: the coating does not have a gradient stacking density coating. Taking the coating slurry as 100% by total mass, the aluminum oxide is 20%, the dispersant sodium polyacrylate and the adhesive polyacrylic acid are 4% by mass fraction of small particle size aluminum oxide, the ether surfactant polyether modified siloxane is 0.5%, and the rest is water.
[0184] Comparative Example 2
[0185] Difference from Example 1: The particle size of aluminum oxide is 800 nm.
[0186] Comparative Example 3
[0187] Difference from Example 1: The positions of the first coating layer and the third coating layer are replaced.
[0188] Comparative Example 4
[0189] Difference from Example 1: The needle-shaped boehmite is replaced by conventional boehmite.
[0190] The electrochemical performance of the batteries prepared in the above examples and comparative examples was tested, and the specific structures are shown in Table 1.
[0191] Table 1 Electrochemical performance
[0192]
[0193]
[0194] From Examples 1-7 and Comparative Examples 1-4, it can be seen that the diaphragm with a gradient stacking density coating provided in the present application still retains good performance in thermal shrinkage, and has more advantages in ionic conductivity, liquid retention rate and electrolyte diffusion rate, and has excellent kinetic properties, which improves the industry pain point of poor kinetics of the current high heat-resistant coating.
[0195] It can be seen from Examples 1-3 and 4-5 that when the mass fraction of the small-particle alumina in the second and third layers of the diaphragm with a gradient stacking density coating is increased, the thermal shrinkage is increased, and the ionic conductivity and liquid retention rate are slightly decreased. This is mainly because the small-particle alumina is filled in the gaps between the needle-shaped boehmite. After the mass fraction is increased, the structural stability is enhanced. At the same time, as an important electrolyte storage layer, it directly affects the liquid retention performance. It can be understood that when the mass fraction of small-particle alumina increases, the heat resistance is improved, but the electrolyte retention performance is reduced, so the mass fraction of the small-particle alumina in the second layer needs to be controlled within an appropriate range; further, the third layer is the surface layer of the coating, which directly affects the wettability of the electrolyte. Since the third layer has the lowest stacking density, it is conducive to the rapid infiltration, penetration and diffusion of the electrolyte on the surface, achieving better coating dynamics.
[0196] It can be seen from Example 1 and Examples 6-7 that after the aspect ratio of the needle-shaped boehmite is increased, the thermal shrinkage performance is slightly attenuated, but the ionic conductivity, liquid retention performance and electrolyte diffusion performance are improved. This is mainly because after the aspect ratio of the needle-shaped boehmite is increased, the packing density of the second and third layers is further reduced, and the coating voids are increased, which is beneficial to electrolyte storage and diffusion, and the kinetics are improved. In order to balance the performance, the aspect ratio of the needle-shaped boehmite needs to be in an appropriate range.
[0197] It can be seen from Examples 1-7 and Comparative Examples 1-4 that when small-particle alumina is replaced by conventional alumina, the packing density of the first coating is greatly reduced, the voids increase, and when subjected to high-temperature impact, the dimensional change increases, and its heat resistance decreases linearly; when the first coating is replaced by the third coating, the powder of the surface small-particle alumina coating is densely packed, which affects the wetting and diffusion of the electrolyte, thereby affecting the dynamics. At the same time, the mixed coating of needle-shaped boehmite and small-particle alumina with more voids in contact with the surface of the substrate has a large dimensional change at high temperature, and the good heat resistance of the diaphragm cannot be guaranteed; when the needle-shaped boehmite is replaced by conventional block boehmite, the wetting and diffusion performance of the electrolyte is greatly reduced, and the diaphragm dynamics deteriorates.
[0198] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
[0199] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.
Claims
1. A diaphragm having a gradient bulk density coating, characterized in that: It comprises a substrate and a coating, wherein at least one side of the substrate is provided with the coating; The raw materials of the coating include aluminum oxide, needle-shaped boehmite, dispersant, adhesive, ether surfactant and water; The coating layer includes multiple layers, the mass content of the aluminum oxide decreases layer by layer from the side adjacent to the substrate to the side away from the substrate, and the mass content of the needle-shaped boehmite increases layer by layer.
2. The diaphragm having a gradient packing density coating according to claim 1, characterized in that: At least one of the following conditions is met: A. The D50 of the aluminum oxide is 100nm-500nm; B. The length of the needle-shaped boehmite is 3 μm-15 μm; C. The aspect ratio of the needle-shaped boehmite is 3-30:1; D. The specific surface area of the needle-shaped boehmite is 6 g / m 2 -12g / m 2 ; E. The thickness ratio of the coating to the substrate is 0.1-1:1; H. The dispersant includes one or more of carboxylate fluorine dispersants, triethyl phosphate, sulfonate fluorine dispersants, sodium polyacrylate, potassium polyacrylate, and polyethylene glycol; I. The adhesive includes one or more of polyacrylic acid, polyacrylonitrile and polyacrylamide; J. The glass transition temperature of the adhesive is ≥150°C; K. The ether surfactant includes one or more of alkylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ether, and polyether-modified polysiloxane.
3. The diaphragm having a gradient packing density coating according to claim 2, characterized in that: At least one of the following conditions is met: A. The D50 of the aluminum oxide is 200nm-400nm; B. The length of the needle-shaped boehmite is 6 μm-12 μm; C. The aspect ratio of the needle-shaped boehmite is 10-20:1; D. The specific surface area of the needle-shaped boehmite is 7 g / m 2 -10g / m 2 ; E. The glass transition temperature of the adhesive is ≥180°C.
4. The diaphragm with a gradient packing density coating according to any one of claims 1 to 3, characterized in that: The coating comprises a first coating, a second coating, and a third coating arranged in sequence, the first coating is adjacent to the substrate, and the coating satisfies at least one of the following conditions: A. The thickness of the first coating is 0.5 μm-2 μm; B. The thickness of the second coating is 1 μm-5 μm; C. The thickness of the third coating is 1 μm-5 μm; D. The mass fraction of aluminum oxide in the first coating is 89.3%-97.1%, and the mass fraction of the needle-shaped boehmite is 0%; E. The mass fraction of aluminum oxide in the second coating is 30%-60%, and the mass fraction of the needle-shaped boehmite is 29.3%-67.1%; G. The mass fraction of aluminum oxide in the third coating is 5%-40%, and the mass fraction of needle-shaped boehmite is 49.3%-92.1%; H. The mass fraction of aluminum oxide in the second coating layer is 10%-40% higher than the mass fraction of aluminum oxide in the third coating layer.
5. The diaphragm having a gradient packing density coating according to claim 4, characterized in that: At least one of the following conditions is met: A. The thickness of the first coating is 0.8 μm-1.5 μm; B. The thickness of the second coating is 2 μm-4 μm; C. The thickness of the third coating is 2 μm-4 μm; D. the mass fraction of aluminum oxide in the second coating is 40%-55%; E. The mass fraction of aluminum oxide in the third coating is 10%-30%; F. The mass fraction of aluminum oxide in the second coating layer is 15%-30% higher than the mass fraction of aluminum oxide in the third coating layer.
6. A method for preparing a diaphragm having a gradient packing density coating according to any one of claims 1 to 5, characterized in that: include: Mixing the raw materials according to different mass contents to obtain a plurality of coating slurries; The plurality of coating slurries are disposed on the surface of the substrate according to the mass content of aluminum oxide from high to low and the mass content of needle-shaped boehmite from low to high, so as to obtain a diaphragm having a gradient packing density coating.
7. The method for preparing a diaphragm having a gradient packing density coating according to claim 6, characterized in that: The mixing includes: first mixing necessary alumina, dispersant, water and non-essential needle-shaped boehmite to obtain a first mixture; second mixing the first mixture and an adhesive to obtain a second mixture; third mixing the second mixture and an ether surfactant; and satisfying at least one of the following conditions: A. The stirring speed of the first mixing is 10rpm-40rpm, the dispersion speed is 1000rpm-3000rpm, and the time of the first mixing is 30min-120min; B. The stirring speed of the second mixing is 10rpm-40rpm, the dispersion speed is 1800rpm-4000rpm, and the time of the second mixing is 60min-180min; C. The stirring speed of the third mixing is 10rpm-40rpm, the dispersion speed is 300rpm-1000rpm, and the time of the third mixing is 20min-60min; D. The setting includes coating and drying.
8. The method for preparing a diaphragm having a gradient packing density coating according to claim 7, characterized in that: The plurality of coating slurries include a first coating slurry, a second coating slurry, and a third coating slurry.
9. A battery, characterized in that: A diaphragm with a gradient stacking density coating prepared by the diaphragm with a gradient stacking density coating as described in any one of claims 1 to 5 or the method for preparing a diaphragm with a gradient stacking density coating as described in any one of claims 6 to 8.
10. An electrical device, characterized in that: A battery comprising the battery of claim 9.
Citation Information
Cited By
Preparation method of composite diaphragm, secondary battery and electric device
CN120033419A
Diaphragm, secondary battery and electric device
CN120978340A